Compliance with radiation protection among radiographers in Eswatini public health facilities - Amelia Shungube; Thandokuhle E. Khoza (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: The consequence of non-compliance with patient radiation safety standards increases unnecessary radiation exposure with high chances of harmful biological effects. Radiographers are trained to prevent these harmful effects by enforcing radiation protection, which is achieved through proper techniques, equipment, shielding materials and beam collimation.